2012
DOI: 10.1016/j.seppur.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of organic foulants behavior on hollow-fiber UF membranes in a drinking water treatment plant

Abstract: a b s t r a c tIn the present work, a ultrafiltration (UF) low pressure membrane (LPM) made of polyvinyl chloride (PVC) was used with an inline poly-ferric sulfate coagulation in a full scale drinking water treatment plant. The organic foulants and their accumulation behavior in the membrane filtration were investigated during a whole year operation. The evolutions of the surface morphology of the membranes were characterized by scanning electronic microscopy (SEM) and atomic force microscopy (AFM). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 36 publications
(43 reference statements)
3
35
0
Order By: Relevance
“…These bands correspond to the carbonyl, amide I, and amide II bands of an amide structure, which would be indicative of proteins (Xiao et al, 2012).…”
Section: Ft-ir Of Organicsmentioning
confidence: 99%
“…These bands correspond to the carbonyl, amide I, and amide II bands of an amide structure, which would be indicative of proteins (Xiao et al, 2012).…”
Section: Ft-ir Of Organicsmentioning
confidence: 99%
“…Each module contains 10 fibers, with an effective length of 23.0 71 cm. The contact angle of the PVC membrane is measured as 33.67170.46, indicating a hydrophilic property [20].…”
Section: The Hollow-fiber Polyvinyl Chloride Membrane Modulementioning
confidence: 99%
“…Xiao et al found that aromatic protein had a highly correlation with irreversible fouling. Humic substances were not found to be important in the formation of the combined fouling layer [36]. And some other studies had showed that the concentration of SMP had a key role in membrane irreversible fouling, while humic substances were not found to be important in the formation of the combined fouling layer [38].…”
Section: Aeruginosa Chlorella Cyclotellamentioning
confidence: 90%
“…Many researches had suggested that the humic substances fraction of natural organic matter (NOM) is a major foulant which controlled the rate and extent of fouling [34,35]. But some other researches had showed that hydrophilic (non-humic) NOM might be a more significant foulant [36]. However, the organic matter in the feed water was important in the membrane fouling process.…”
Section: Aeruginosa Chlorella Cyclotellamentioning
confidence: 99%